دراسة بيئية وتصنيفية لرخويات المياه العذبة في بعض الأوساط في المنطقة الساحلية السورية (نهر الحصين) (Latakia University Journal -Basic Sciences Series, 2018)
لقد تم اختيار أربعة عشر وسطاً مائياً عذباً في المنطقة الساحلية من القطر العربي السوري تختلف بصفاتها الحيوية واللاحيوية، وقد جمعت العينات بشكل منتظم مرة كل خمسة عشر يوماً لمدة تسعة عشر شهراً اعتباراً من 12/3/1999 ولغاية 20/10/2000، ثم أخذت عينات مراقبة شهرية من هذه الأوساط اعتباراً من 20/10/2000 ولغاية 12/1/2001. لقد تم التعرف على 33 نوعاً من صف الرخويات بطنية القدم Gastropodoa (20 نوعاً من تحت صف أمامية الغلاصم Prosobranchia و13 نوعاً من تحت صف الرئويات Pulmonata) وثلاثة أنواع من صف ثنائية المصراع Bivalvia. لقد تم إجراء دراسة هيدروبيولوجية لأحد الأوساط المائية وهو نهر الحصين حيث درست صفات الوسط اللاحيوية، وكذلك بيئة أحد الأنواع الأكثر غزارة في الوسط وهو النوع Physa acuta من حيث حركية جماعته التي أظهرت وجود فترتين للتكاثر الأولى ربيعية هامة والثانية خريفية أقل أهمية وإلى أن عمر الأفراد يصل إلى حوالي 9 أشهر تقريباً. كما تمت دراسة بنية الجماعة التي أوضحت القياسات الحيوية لأفراد النوع ولمنتجاته التناسلية والعلاقة بين طول القوقعة ووزنها الجاف وكذلك طول القوقعة وعرضها. Fourteen freshwater sampling locations from the Syrian coastal region, differing in their biotic & abiotic features,  were chosen.  Samples were collected fortnightly on regular basis for a period of  nineteen months (12/3/1999 till  20/10/2000).  Monitoring monthly samples were collected from these localities starting  from 20/10/2000 till 12/1/2001. Thirty three species of Gastropods (20 of Prosobranchia and 13 of Pulmonata) and three species of Bivalvia were identified. A Hydro-biological study of one locality (Al Housien river) was conducted and  the Abiotic features were looked for.  In addition,  the ecology of the most abundant species, Physa acuta,  was studied and its population dynamic  was monitored.   Two spawning periods, one is  in the spring which is more important, and the other is in the Autumn, were detected and the individual age is found to be up to 9 months.  In addition, the population structure was studied, which clarified the biological measurements of the species individuals & its sexual products and the relationship between shell length & each of the dry weight and the width.